My House, my Fragmented City: The Brazilian Social Housing Programme “Minha Casa, Minha Vida” in the cases of Manaus and Belém - Moreno Pessôa, Igor Tempels (A+BE | Architecture and the Built Environment, 2019)
This study investigates the relationship between housing policy and spatial fragmentation, specifically in the case of the social housing programme in Brazil called “Minha casa, minha vida”(MCMV - Portuguese for “my house, my life”). As the title of the programme suggests, it aims to improve life quality by increasing housing quality and home ownership, but this article demonstrates that the programme can have a substantial negative impact at the wider urban scale promoting spatial fragmentation. Two case studies are analysed: the cities of Manaus and Belém. The research involved the development of maps using GIS technology crossing data related to spatial fragmentation and the MCMV programme. By creating maps that incorporate these data, it is possible to observe that the MCMV programme is reinforcing existing spatial fragmentation in Manaus and Belém. The article concludes that even though the MCMV social housing programme has had a positive impact on increasing home ownership in the low-income segment, it has also had an adverse impact by reinforcing spatial fragmentation at the city level.